2019
DOI: 10.1590/0100-3984.2018.0089
|View full text |Cite
|
Sign up to set email alerts
|

The role of gadoxetic acid-enhanced magnetic resonance cholangiography in the evaluation of postoperative bile duct injury: pictorial essay

Abstract: Iatrogenic lesion of the bile ducts is a relatively common occurrence during liver surgery, increasing morbidity and mortality rates. T2-weighted magnetic resonance cholangiography and gadoxetic acid-enhanced functional magnetic resonance cholangiography (fMRC) with administration of hepatobiliary-specific contrast medium (gadoxetic acid) are fundamental to the diagnostic imaging approach in patients with such lesions. Here, we present a review of the literature and suggest an imaging approach to biliary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
5
0
4
Order By: Relevance
“…Several authors [181][182][183][184][185] confirmed that the additional use of contrast-enhanced MRCP (CE-MRCP) using 3D and 2D T1-weighted images acquired at the hepatobiliary phase after hepato-specific contrast agent injection improves the accuracy of bile anatomy depiction and bile leak detection. In a series of 99 patientsincluding 24 followed after cholecystectomy, 20 after surgical reconstruction of traumatic BDI, and 16 after hydatid cystectomythe use of CE-MRCP increased the sensitivity, specificity, and accuracy, with respective ranges (depending on the bile leak etiology) of 76-82%, 100%, and 75-91% compared to 53-63%, 51-66%, and 55-63% observed with conventional MRCP [183].…”
Section: Imaging For Postoperative Diagnosis Of Bdimentioning
confidence: 96%
“…Several authors [181][182][183][184][185] confirmed that the additional use of contrast-enhanced MRCP (CE-MRCP) using 3D and 2D T1-weighted images acquired at the hepatobiliary phase after hepato-specific contrast agent injection improves the accuracy of bile anatomy depiction and bile leak detection. In a series of 99 patientsincluding 24 followed after cholecystectomy, 20 after surgical reconstruction of traumatic BDI, and 16 after hydatid cystectomythe use of CE-MRCP increased the sensitivity, specificity, and accuracy, with respective ranges (depending on the bile leak etiology) of 76-82%, 100%, and 75-91% compared to 53-63%, 51-66%, and 55-63% observed with conventional MRCP [183].…”
Section: Imaging For Postoperative Diagnosis Of Bdimentioning
confidence: 96%
“…Níveis altos destas últimas indicam a provável existência de uma lesão vascular e são mais indicativas de uma progressão para cirrose biliar secundária. 1 Para o diagnóstico de imagem, a tomografia computadorizada e ultrassonografia apresentam limitações, ficando restritos para detectar dilatação das vias biliares e coleções peri-hepáticas, entre elas, a bile livre na cavidade abdominal 1,3,13,14 . Colangiopancreatografia endoscópica retrógada também pode ser utilizada em casos selecionados, pois além do estudo da via biliar, é possível realizar intervenções em ductos biliares menores, através da colocação de próteses, porém, possui desvantagens importantes, tais como o fato de ser um procedimento invasivo e o elevado risco de complicações, como por exemplo sangramento intraluminal e sepse.…”
Section: Diagnósticounclassified
“…Colangiopancreatografia endoscópica retrógada também pode ser utilizada em casos selecionados, pois além do estudo da via biliar, é possível realizar intervenções em ductos biliares menores, através da colocação de próteses, porém, possui desvantagens importantes, tais como o fato de ser um procedimento invasivo e o elevado risco de complicações, como por exemplo sangramento intraluminal e sepse. 11,14 A colangiografia por ressonância magnética apresenta-se como ótima opção, por se tratar de uma modalidade não invasiva e com sensibilidade de 85%-100%, sendo portanto o exame considerado como padrão ouro para abordagem pré-operatória de pacientes com LIVB. 1 Uma técnica promissora, a colangiografia por ressonância magnética com contraste hepato-específico, o ácido gadoxético, já apresentou utilidade em delinear a anatomia da árvore biliar pré-operatória e pós-operatória, bem como em detectar e caracterizar doenças biliares e complicações cirúrgicas, entre elas: cálculos, estenoses, fístulas e cistos biliares.…”
Section: Diagnósticounclassified
See 1 more Smart Citation
“…Several studies confirmed that the additional use of contrast-enhanced MRCP at the hepatobiliary phase after hepato-specific contrast agent injection using 3D and 2D T1-weighted images acquired improves the accuracy of bile anatomy depiction and bile leak detection (DeAngelis et al, 2021). A study of 99 patients that included 24 patients after cholecystectomy, 20 after surgical reconstruction of traumatic BDI, and 16 after hydatid cystectomy, concluded that the use of contrast-enhanced MRCP increased the sensitivity, specificity, and accuracy with ranges of 76-82%, 100%, and 75-91% compared to 53-63%, 51-66%, and 55-63% observed with conventional MRCP (Park et al, 2004;An et al, 2006;Lee et al, 2009;Cieszanowski et al, 2013;;Kantarc et al, 2013;Wong et al, 2018;Ribeiro et al, 2019). The optimal timing for hepatobiliary phase acquisitions with contrast-enhanced MRCP appears to range between 60 and 90 min when looking for bile leaks (Cieszanowski et al, 2013;Wong et al, 2018) The main aim of this study was to evaluate the impact of iatrogenic post-cholecystectomy BDI on the amount of a wide array of diagnostic imaging and hospital re-admission rate.…”
Section: Introductionmentioning
confidence: 99%